Benefit distribution of integrated regional energy systems under carbon trading mechanisms based on improved Shapley value methods - Wang, Yubao; Cao, Rongyu; Luo, Da; Li, Pengpeng; Cheng, Xiang (Frontiers in Energy Research, 2023)
Carbon trading mechanisms and the development of integrated energy systems are important ways to realize the “carbon peaking and carbon neutrality” goal, and the problem of benefit distribution is of paramount importance to achieving the goal. The article innovatively takes the supply side of the provincial integrated energy system as the entry point, considers the economic value of carbon, and focuses on the rational allocation of each subject obtained by comparing different methods. The paper mainly uses the Shapley value of the cooperative game and the kernel method to establish the initial allocation to the main actors, and subsequently, it considers the introduction of the risk level, resource input, environmental pollution, technological innovation, and profit of the main actors to modify the result of the benefit allocation. This paper takes the power generation data of the Xinjiang region as an example, and the results show that 1) thermal power still has the most weight among all power generation modes and obtains 522.83, 503.48, and 406.30 billion yuan under the initial, nucleolus, and modified allocation methods, respectively, and receives the most revenue. 2) Considering that the multi-factor allocation method pays more attention to the allocation of fairness, compared with the initial allocation, thermal power gains decreased by 22.29%, while wind and solar power gains were improved by 17.87% and 60.90%, respectively. The result could be a stronger push for the development and transformation of power energy. 3) The feasibility of this game as a convex game should be verified, the improvement method should be demonstrated through examples, and the results should be compared with reality. Finally, policy recommendations are proposed, which will be useful for realizing the “carbon peaking and carbon neutrality” goal and the synergistic development of integrated energy systems.